Development of an integrated vocational interest website for high school students' career interest assessment - Bagaskara, Rafli Sodiq; Itsnaini, Afifah Ulayya; Dewanti, Novellia Ardhya; "˜Azmi, Syahrul Maula (Psychological Research and Intervention, 2023)
"Wrong major phenomena" are increasingly common these days. One reason is that students do not truly understand their personalities and the activities to which they are naturally inclined. Therefore, assessing career interests is crucial for high school students aspiring to continue their studies at university. Holland's Structure of Interest is one vocational interest construct used for assessment tools that could help solve this problem by identifying interest types that align with job characteristics. Unfortunately, psychological assessment services are limited in Indonesia. Integrated vocational interest website development must be undertaken so that people can access these psychological services more widely and minimize human error. The website development method refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). A prototype version of the Integrated Vocational Interest website could provide job and major recommendations to students based on their interest types. These results indicate that the vocational interest website has great potential to help students avoid the "wrong major" phenomenon.